Uterus didelphys: the first case report on molecular profiling of endometrial tissue from both uterine cavities - Alberto Sola-Leyva; Bárbara Romero; Analuce Canha-Gouveia; Inmaculada Pérez-Prieto; Nerea M. Molina; Eva Vargas; Juan Mozas-Moreno; Clara Chamorro; Merli Saare; Andres Salumets; Signe Altmäe (Reproductive Biology and Endocrinology)
Abstract Background A didelphic uterus represents a unique and infrequent congenital condition in which a woman possesses two distinct uteri, each with its own cervix. This anomaly arises due to partial or incomplete merging of the Müllerian ducts during the developmental stages in the womb. Accounting for uterine malformations, a didelphic uterus is a relatively rare condition, affecting approximately 0.5–2% of the population and is considered one of the more uncommon types of uterine abnormalities. Methods This case report aims to study the physical separation in uterine didelphys and its impact on endometrial microbiome and inflammation, and the patterns of endometrial receptivity observed. Results Endometrial receptivity analyses revealed a similar receptive state in both uteri, both in the early receptive phase. Differential markers of chronic endometritis, including CD138, and MUM1-positive cells, were observed when comparing endometrial biopsies from both uteri. The right uterus exhibited a higher prevalence of these positive cells. Regarding the microbiome, significant differences were found between the uteri, notably in the right uterus, a clear non-dominance of lactobacilli and the presence of genera such as Staphylococcus, Streptococcus, and Acinetobacter. Additionally, the right uterus presented a less ‘favourable’ microenvironment, a characteristic that was also reflected in the right cervix; both sites presenting less lactobacilli than the left side samples. A distinct metabolomic signature associated with the physical separation of the uteri contributed to the differences in endometrial milieu. Conclusions Our study revealed that physical separation, among other factors in uterus didelphys, affects the endometrial microbiome, metabolome, and inflammatory state, with significant microbiome variation observed between the uteri, although similar endometrial receptivity patterns were noted.